Thermodynamic parameters and characterization of poly(methyl methacrylate) with some probes using inverse gas chromatography - Kaya, Ismet; Özdemir, Eyüp; Coşkun, Mehmet (Marcel Dekker Inc., 1996)
Activity coefficient ?1?, Flory-Huggins interaction parameters ?12 and partial molar free energy of mixing at infinite dilution ?G1? ,for solutions of poly (methyl methacrylate) (PMMA) with alkanes, ketones, acetates, aromatic and alcohol at temperatures ranging from 433°K to 473°K have been obtained from inverse gas chromatography retention data. Five different families with different chemical nature and polarity were used to obtain some insights about PMMA-solvent interactions. The PMMA-solvent interaction parameters and the free energy of mixing were found at a series of temperature.The glass transition temperature and melting point of PMMA is found 110°C and 170°C, respectively.The thermodynamic sorption functions for the sorption process of the different chemical nature of probes into PMMA solution were obtained and discussed in terms of their interactions with PMMA. Furthermore, the contributions of CH2, C=O, C=O-OR, aromatic and OH functional groups in the five series to the sorption process were also obtained. Acetates, ketones and methanol were found to be good solvents for PMMA, and alkanes and o-xylene were found to be non-solvents of PMMA. Copyright © 1996 by Marcel Dekker, Inc.